Staying cool or staying safe in a human-dominated landscape: which is more relevant for brown bears? - Ordiz, Andrés (Oecologia, 2017)
Pigeon et al. (2016) Staying cool in a changing landscape: the influence of maximum daily ambient temperature on grizzly bear habitat selection. Oecologia 181:1101. doi:10.1007/s00442-016-3630-5 analyzed the effect of ambient temperature on the habitat selection of grizzly bears (Ursus arctos) in Alberta, Canada. They concluded that temperature played a significant role in bear habitat selection and that it was unlikely that human activity introduced biases to the habitat selection of bears. However, Pigeon et al. did not consider variables related to human activities in their analyses. They also misinterpreted previous research that has accounted for temperature in the habitat selection of brown bears. There is much literature published on the negative effects of human disturbance on wildlife in general and on bears in particular. Downplaying the role of human disturbance could have important negative consequences if, in fact, human disturbance were a more important factor than thermoregulation. Indeed, dismissing the importance of human influence, in the face of contradictory evidence, could tempt managers to disregard an important factor that is difficult and often unpopular to deal with in their conservation plans.